Characteristics of Ultisols derived from basaltic andesite materials and their association with old volcanic landforms in Indonesia - Purwanto, Setiyo; Gani, Rachmat Abdul; Suryani, Erna (Universitas Sebelas Maret, 2020)
The common problem with Ultisols is their low pH and soil fertility, with liming and fertilization being common solutions to overcome this problem; however, studies on Ultisol soil parent materials are still rare. This study aimed to examine the characteristics of Ultisols derived from andesite and basaltic andesite parent materials. In 2016–2017, five Ultisol pedons (P8, P9, P10, P11, and P15) were sampled from basaltic andesites and other associations. The five pedons consisted of 19 soil samples. The chemical and mineralogical properties of the soils were analyzed. It was found that the color of the basaltic andesite Ultisols varied from hue of 2.5 YR to 10 YR, with value of 3–5 and chroma of 2–8. The Ultisols derived from andesite/diorite (P8) were dominated by rock fragments (52–77%), while those derived from andesitic breccia (P9) were dominated by opaques (62–67%), those from basaltic andesite tuff/lava by weathering minerals (44–52%) and hydragilite (28–34%), those from basaltic andesite (P11) by quartz (48%) and (P15) by opaques (79–89%). The mineral reserves varied from very low (0–4%) in pedons P8, P9, P11, and P15 to very high (> 40%) in pedon P10. The results of this study are expected to be used as a guide for future agricultural development on Ultisols.